antimicrobial and antiradical activities evaluation of essential oils, ethanolic and hydroethanolic extracts of the leaves of Eucalyptus citriodora hook from Benin - YAYA, Koudoro; AGBANGNAN, DOSSA COKOU PASCAL; YEHOUENOU, BONIFACE B.; TCHOBO, PAUL FIDÈLE; ALITONOU, GUY ALAIN; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2014)
The precipitation and coloration reactions implemented in this study revealed in the leaves of E. citriodora (Myrtaceae) of Benin the presence of polyphenols, anthocyanins, flavonoids, saponins, tannins, mucilages, anthraquinones, leucoanthocyanins, cardiac glycosides, coumarins, proteins, sterols and triterpenes. The essential oil from the leaves of this plant was extracted with a yield of 3% and then analyzed by GC/MS. Nine compounds, representing 94.46% of the chemical composition of the oil, were identified, three among them being majority: citronellal (65.45%), citronellol (13.5%) and isopulegol (10.33%). The contents of polyphenolic compounds of ethanolic and hydroethanolic extracts were respectively 4.52 mg EAG.g-1 and 4.38 mg EAGg-1 for total polyphenols, 78.76 mgECg-1 and 81.56 mg ECg-1 for total flavonoids and 62.62 mg ECg-1 and 67.09 mg ECg-1 for condensed tannins. The radical scavenging activity of hydroethanolic extract (IC50=0.23 mgmL-1) was more pronounced than that of ethanolic extract (IC50=0.42 mgmL-1) and essential oil (IC50=0.9 mgmL-1). Regarding antimicrobial activity, Staphylococcus aureus and Candida albicans were sensitive to hydroethanolic extract of E. citriodora leaves while Escherichia coli developed resistance against this extract. As for the essential oil extracted from the leaves of Eucalyptus citriodora it showed fungicidal activity against Candida albicans and bacteriostatic with Escherichia coli and Staphylococcus aureus.
Keywords: Candida albicans; Escherichia coli; essential oil; polyphenoliccompounds; radical scavenging